The Physical Parameters, Stability, and Habitability of some Double-lined Spectroscopic Binaries - Alameryeen, H. A.; Abushattal, A. A.; Kraishan, A. F.
Large ground telescopes can now resolve most double-lined binaries optically at some point in their orbit due to the improvement of imaging techniques in recent decades. Using additional information about these systems, such as astrometric parallax, even a single precise visual observation can provide a 3D orbit and the primary physical parameters. Furthermore, both the visual and spectroscopic orbits can be determined. We combine the Edward method with the visual solution and the spectroscopic orbit parameters: period (P), periastron epoch (T), eccentricity (e), semimajor axis (a1,2) and inclination (i), we also know the mass ratio of the system. The developed method allows us to select doublelined spectroscopic systems with recently calculated orbits. We calculate the individual masses, orbital parallax, and other fundamental astrophysical parameters. The purpose of these parameters is to verify the reliability of the data received from space missions and to calculate the stability and habitability, which is the primary goal of this study. Astronomical information can be obtained from binary stars. By observing short period binaries using both spectroscopy and interferometry, we can determine the individual masses and orbital parallaxes of the objects based on their corresponding orbits. Spectroscopic binaries with double-lines are therefore fundamentally important to optically resolve. To determine the required telescope aperture for the resolution of a spectroscopic binary, we developed a specific algorithm. We determined the most probable maximum and minimum separations between each spectroscopic binary based on photometric and spectroscopic information. Thus, we also determined the different physical parameters of each system by using the calibrations we obtained in our study. Based on optically resolved spectroscopic binaries with both spectroscopic and visual orbits, the methodology presented here was successfully tested.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture